Calcined Corncob-Kaolinite Combo as New Sorbent for Sequestration of Toxic Metal Ions From Polluted Aqua Media and Desorption - Chukwuemeka-Okorie, Helen O.; Ekemezie, Peter N.; Akpomie, Kovo G.; Olikagu, Chisom S. (Frontiers in Chemistry, 2018)
This study investigated a new area of improving the adsorption capacity of clay using corn cob as an alternative means of clay modification to the more expensive and complicated chemical treatment techniques. Kaolinite Clay (KC), Calcined corncob-kaolinite Combo (CCKC) and Corncob (CC) adsorbents were utilized. The adsorbents were characterized by Fourier Transform-Infrared (FT-IR) Spectroscopy, Scanning Electron Microscopy (SEM), X-ray fluorescence spectroscopy and Brunauer-Emmett-Teller (BET) surface area analyzer. Batch adsorption methodology was used to investigate the effect of pH, initial metal concentration, adsorbent dose, and contact time on adsorption of Pb (II) and Cd (II). A slight increase in BET surface area of 29.31m2/g for CCKC from 14.12 m2/g for raw KC was achieved. The trend of metal adsorption on the adsorbents was in the order CC>CCKC>KC. The Langmuir isotherm was found to present the best fit for the unmodified adsorbents while the Freundlich was applicable for CCKC indicating multilayer heterogeneous surface. The pseudo second order kinetic model was found to be suitable in the kinetic analysis. Thermodynamic studies revealed a spontaneous physical adsorption process of metal ions on CCKC. The combo adsorbent showed highest percentage desorption (> 70%) of Cd and Pb ions in both acid and basic media compared to the other adsorbents. The results of the study established the efficiency of calcined corn cob kaolinite combo as suitable adsorbent for metal ions.